Technique for Isolation of Malicious Nodes from the Cloud Computing Architecture (International Journal of Engineering and Computer Science, 2017)
The cloud computing is the architecture in which virtual machine, cloudlets, and data centers are involved in communication. In the network, malicious nodes are responsible to trigger various types of active and passive attacks which reduce network performance in terms of various parameters. In this work, technique will be proposed for the detection and isolation of malicious nodes from the network. the malicious nodes are responsible to trigger virtual side channel attack in the network.